2008
DOI: 10.1007/s00431-008-0894-8
|View full text |Cite
|
Sign up to set email alerts
|

Family-based group treatment versus individual treatment in the management of childhood obesity: randomized, prospective clinical trial

Abstract: These findings demonstrate that the group treatment is more successful than the individual treatment in the management of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 31 publications
0
56
0
4
Order By: Relevance
“…Criterion validity was evaluated in 10 diet dairy papers, with many reporting significant effects of weight, BMI or other measures of adiposity on validity. 55,[57][58][59][60][61][62][63] The only paper that reported no misreporting by body weight was O'Conner et al 64 in their study of 45 children. This paper 64 reports low relative bias [mean difference, energy intake (EI) -total energy expenditure (TEE) = at 118 kJ/day] but with wide LOA (bias plus or minus two standard deviations of the difference) at 118 ± 3345 kJ/day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criterion validity was evaluated in 10 diet dairy papers, with many reporting significant effects of weight, BMI or other measures of adiposity on validity. 55,[57][58][59][60][61][62][63] The only paper that reported no misreporting by body weight was O'Conner et al 64 in their study of 45 children. This paper 64 reports low relative bias [mean difference, energy intake (EI) -total energy expenditure (TEE) = at 118 kJ/day] but with wide LOA (bias plus or minus two standard deviations of the difference) at 118 ± 3345 kJ/day.…”
Section: Resultsmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64] Of these, one 56 tested inter-rater reliability using a tape-recorded method, with correlations ranging between 0.68 and 0.96. None of the papers assessed TRT reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Dieses (Moens et al, 2010;Sacher et al, 2010;Garipagaoglu et al, 2009;Golan u. Crow, 2004;Wilfley et al, 2007).…”
Section: Prädiktorenunclassified
“…Their definition of family behavioral treatment does not indicate that any of the key principles of FCC were considered or practiced during interactions with families . These findings are significant as modest weight loss has been associated with significant health improvement and a reduction in overall risk of morbidity and mortality in obese children (Garipagaoglu, Sahip, Darendeliler, Akdikmen, & Kopuz, 2008). Young et al (2007) also demonstrated that weight loss achieved using family based management strategies is achievable and can be maintained short term.…”
Section: Young Et Al (2007) Provide Strong Evidence That Weight Lossmentioning
confidence: 67%
“…This is important as it provides evidence that children presenting with non modifiable risk factors can successfully lose weight, decrease their risk of morbidity and mortality and maintain their weight loss over time. Garipagaoglu et al (2008) published a study to assess the short and long term effects of a three month family based group treatment in the management of childhood obesity versus individual treatment. It involved 80 obese children between 6 and 14 years.…”
Section: Effect Of Family Centered Care Initiatives On Long-term Weigmentioning
confidence: 99%